On solution of Fredholm integral equations via fuzzy b-metric spaces using triangular property - Gunaseelan Mani; Arul Joseph Gnanaprakasam; Absar Ul Haq; Imran Abbas Baloch; Choonkil Park (AIMS Mathematics, 2022)
In the present paper, we prove common fixed point without continuity by using triangular property on fuzzy b-metric space. Our results generalize and expand some of the literature's well-known results. We also explore some of the application of our key results to Fredholm integral equation.